The urgency of social-creativepreneurship competency in social studies learning during the Covid-19 pandemic: Teachers perception - Anik Widiastuti; Nana Supriatna; Disman Disman; Siti Nurbayani (Jurnal Cakrawala Pendidikan, 2023)
Distance learning carried out in Indonesia during the Covid-19 pandemic allowed learning loss to occur due to the ineffectiveness of the implementation of learning. In this regard, students need to be provided with relevant competencies, one of which is social-creativepreneurship competency through Social Studies learning. This study is intended to investigate teachers perception about the urgency of the integration social-creativepreneurship competency in Social Studies learning during the Covid-19 pandemic as life skills for students. The method used is descriptive survey using an open questionnaire in google form format. The research respondents obtained were 68 Social Studies teachers at Junior High Schools in Yogyakarta. The data collected were analyzed descriptively. The findings are: 1) 81% teachers stated that the social-creativepreneurship competency is “urgent” to integrate in Social Studies learning, and 19% stated that “very urgent”; 2) 86% of teachers expressed interest in integrating social-creativepreneurship competencies in Social Studies learning, 10.29% were very interested, and 2.95% were quite interested; 3) social-creativepreneurship competency can be integrated into sub-themes: economic activities, markets and inter-regional and inter-island trade, as well as creative economy and international trade carried out using demonstration, observation, selling project, role playing, interview, and social problem solving based learning.